Effects of dietary methyl donors on health status in blue fox (Alopex lagopus) vixens given a low protein diet during body fat mobilisation - Nenonen, Nita; Nieminen, Petteri; Dahlman, Tuula; Valaja, Jarmo; Pölönen, Ilpo; Anttila, Marjukka; Mustonen, Anne-Mari; Rekilä, Teppo (International Fur Animal Scientific Association (IFASA), 2004)
v 2004 ok